Residual mechanical properties of steel fibre reinforced geopolymer concrete (SFRGC) after exposure to elevated temperatures - Hosan, Md Anwar (Curtin University, 2016)
This study presents the effects of two types of alkali activators (Na and K-based) on the residual mechanical properties of steel fibre reinforced geopolymer concretes (SFRGC) after exposed to various elevated temperatures and compared with those of steel fibre reinforced concrete (SFRC). Results show that the SFRGC containing Na- based activators exhibited much higher residual compressive and indirect tensile strength at all elevated temperatures including at ambient condition than its K-based counterpart and SFRC.